Panduan untuk pengembangan, pengujian dan pemilihan kriteria dan indikator untuk pengelolaan hutan lestari - Prabhu, Ravi; Colfer, C.J.P.; Dudley, R.G. (Center for International Forestry Research, 2000)
This manual provides methods for the development and evaluation of criteria and indicators (C&I) which can then be used to assess the sustainability of forest management. The manual is written primarily for researchers, people or groups interested in evaluating C&I for assessments of forests in new areas, or as a reference for readers wanting to know how CIFOR's Generic Template was produced. The methods presented are aimed at the development of sets of C&I for natural forest at the forest management unit level, especially in the tropics. Following an introductory chapter focusing on the overall purpose, specific objectives, and the C&I development process, three chapters explain how to prepare for C&I testing, how to conduct a test, and how to analyse the results. Subsequent chapters explain the conceptual basis of C&I development, with three case studies offered as examples, and suggested additional reading materials. Specific forms and tools that have been used in the course of CIFOR's testing are also presented, with examples of ways to present the results. The final chapter provides possible baseline sets of C&I, available to users for evaluation and testing in their own contexts.